Uso de e-Learning para integrar en el empowerment a los recursos humanos de la empresa financiera Mibanco del distrito de Jaén - Requejo Delgado, Freddy Omar (2013)
This following research seeks to improve empowerment matters, into reviewers using eLearning resources, during the research has shown that eLearning resources has consolidated a more comprehensive training and access to mediation of knowledge and attitudes of partners MiBanco. Empowerment in the process of continuous training of employees requires mediation resources that are able to socialize and also build tools for measuring achievements in each employee, this enables both employees and management know what has been the progress of each , and give recognition to those respective achievements. For the investigation a sample of 24 employees has been chosen, with a confidence level of 90 %, the research design was a pre - experiment with pretest and posttest. The study found that there is significant progress in the integration of eLearning empowerment when used as an element of fundamental mediation in learning and attitudes of employees. Moreover, it was identified that the cost - benefit ratio is the best in the use of eLearning resources to enhance capabilities in the field of human resources management.